Entrepreneurial Leadership and Business Performance of MSMEs: The Mediating Role of Government Support - Gretchen Dawaton Bangguiyac; Marc Oliver Castañeda (AIBPM Publisher, 2025)
Micro, small, and medium enterprises (MSMEs) play a vital role in promoting economic growth, especially in rural areas with limited access to employment and livelihood opportunities. This study examined the relationship between entrepreneurial leadership and the business performance of MSMEs in Kalinga, Philippines, with government support as a mediating variable. Using an explanatory correlational design, data were collected from 336 MSME owners through a validated questionnaire. Structural Equation Modeling (SEM) was employed to analyze the relationships among the variables. Findings reveal that among entrepreneurial leadership dimensions, absorbing uncertainty (? = 0.254, p = 0.004) and creative collective self-efficacy (? = 0.220, p = 0.001) significantly and positively impact MSME business performance, while defining gravity shows a significant negative effect (? = -0.102, p = 0.015). Other entrepreneurial leadership dimensions show no significant effect. Government support positively influences performance (? = 0.063, p = 0.0058) but only partially mediates the effect of creative collective self-efficacy (? = 0.017, p = 0.019), contributing 7% mediation. These findings underscore the need for aligning government support to enhancing entrepreneurial leadership strengths to improve the business performance of MSMEs.